Cold compared with room temperature compress on the repaired primiparous perineum following injury at normal vaginal delivery: A randomized controlled trial - Karim, Khaliza Kazrin (Elsevier Inc., 2024)
BACKGROUND: The perineum is typically injured at the first vaginal birth. The application of a cold compress to the perineal repair site can reduce pain; however, the effect usually dissipates after a couple of hours. Repeated applications may be needed for sustained analgesia. However, the medium-term effect of repeated applications of cold compress on the perineal repair site on the recovery of sexual function and perineal healing is not known. OBJECTIVE: This study aimed to evaluate repeated applications of cold vs room temperature (placebo control) compress to the repaired primiparous perineum on pain upon movement. STUDY DESIGN: A randomized controlled trial was conducted in a university hospital in Malaysia from May 2022 to February 2023. A total of 224 women with a repaired episiotomy or spontaneous second-degree tear sustained at normal delivery were randomized as follows: 113 to frozen gel pack and 111 to room temperature gel pack, as wound compress. The compress was applied to the perineal repair site at 3 timepoints: immediately after repair, and at 4 and 8 hours after delivery, for 20 minutes at each application. The primary outcomes were pain during movement at 12 and 24 hours after delivery, scored using the 0 to 10 numerical rating scale. The secondary outcomes include duration of hospital stay; analgesic consumption; recovery and functional metrics of reestablishing flatus, mobilization, and urination, breastfeeding; maternal satisfaction with the allocated compress; and after hospital discharge for up to 6 weeks after birth through telephone interview, analgesic consumption, perineal pain, resumption of vaginal sex, and women's perception of perineal wound healing. RESULTS: The median (interquartile range) of pain at movement scores were 4 (4–5) vs 5 (4–5) (P=.018) at 12 hours and 2 (1–3) vs 2 (2–3) (P=.173) at 24 hours after birth for cold vs room temperature compress, respectively. Maternal satisfaction scores were 8 (7–9) vs 7 (6–8) (P=.119), oral analgesic for perineal pain while at the postnatal ward was taken by 94 of 113 (83.2) vs 85 of 109 (78.0) (relative risk, 1.07; 95 confidence interval, 0.94–1.21), and time to the first satisfactory breastfeeding episode was 11.6 (7.9–15.5) vs 13.0 (8.0–20.7) hours (P=.303) for cold vs room temperature compress, respectively. At 2 weeks telephone follow-up, analgesic intake and perineal pain were not different. At 6 weeks, analgesic intake, perineal pain, resumption of vaginal sex, exclusive breastfeeding, and maternal perception of perineal healing were not different. CONCLUSION: Intermittent cold compress in the first 8 hours to the repaired perineum reduces pain at 12 hours but the effect attenuates by 24 hours. Maternal satisfaction with their allocated compress was not different. There was no suggestion of harm or benefit on the other secondary outcomes. © 2023 Elsevier Inc.